Pengabdian Kepada Masyarakat: Peningkatan Literasi Visual dan Kesadaran Spasial Siswa SMAN 10 Batang Hari melalui Program “Arsitektur untuk Semua” - Brama Nalendra; Shinta Oktaviana; Badariah Badariah; Latusi Anggriani; Saldi Yulistian; Syahidullah Habibie; Randy Rizal (SIGMA : Jurnal Sinergi Mengabdi, 2026)
The quality of the built environment is known to significantly influence students' psychological well-being and learning creativity; however, visual literacy and spatial awareness are rarely taught explicitly in general high school curricula. This community service initiative aimed to introduce basic architectural concepts to students at SMA Negeri 10 Batang Hari to foster their visual awareness and spatial understanding. The approach employed architectural pedagogy through interactive lectures and discussions, involving seven lecturers from UIN Sulthan Thaha Saifuddin Jambi. The material covered fundamental architectural elements, aesthetic principles, and the relationship between humans and space. The results indicate that students gained a new perspective on their school and home environments, viewing them no longer merely as physical structures but as meaningful spaces. The activity successfully stimulated critical thinking regarding design aspects and spatial function, although future continuity would require practice-based workshops—such as drawing or model-making—to allow for the concrete application of the knowledge gained. Overall, this program helped bridge the gap between architectural education and the general public while nurturing a generation more attuned to the quality of their surrounding built environment.